Peri-Articular Injection of Tranexamic Acid Reduce Blood Loss and Transfusion Requirement During Total Knee Arthroplasty: A Meta-analysis - Yue Liu MD; Duo Shan MD; Peng Tian MD; Zhi-jun Li MD; Gui-jun Xu MD; Xin Fu MD (Geriatric Orthopaedic Surgery & Rehabilitation, 2022)
Background The aim of this meta-analysis was to evaluate the efficacy and safety of peri-articular injection of tranexamic acid (TXA) during total knee arthroplasty (TKA) from clinical controlled trials. Method Eligible scientific articles published prior to October 2021 were retrieved from the PubMed, Springer, ScienceDirect and Cochrane Library databases. The statistical analysis was performed with RevMan 5.1. Result 2 RCTs and 3 non-RCTs met the inclusion criteria. Meta-analysis showed significant differences in terms of hemoglobin reduction (MD = −1.04, 95% CI: −1.33 to −.76, P < .00001), total blood loss (MD = −342.80.70, 95% CI: −437.52 to −248.08, P < .00001), drainage volume (MD = −297.24, 95% CI: −497.26 to −97.23, P = .004) and blood transfusion rate (OR = .30, 95% CI: .14 to .62, P = .001) were found in the control group. No postoperative infection and deep venous thrombosis were found between 2 groups. Conclusion Peri-articular injection of TXA can effectively decrease perioperative blood loss and blood transfusion rate without increasing the incidence of postoperative complications during TKA.